The Role of Thickening Agent Proportions in Optimizing Nanoemulsion Gel for Dermatophytosis Treatment - Zhang X; Wu CC; Jiang H; Zhao JF; Pan ZJ; Zheng Y (International Journal of Nanomedicine)
Xiao Zhang,1,* Chen-Chen Wu,1 Hua Jiang,2 Jia-Fu Zhao,1,3 Zhong-Jian Pan,1 Yin Zheng1,3,* 1College of Animal Science, Guizhou University, Guiyang, Guizhou, People’s Republic of China; 2College of Veterinary Medicine, Gansu Agriculture University, Lanzhou, Gansu, People’s Republic of China; 3Key Laboratory of Animal Genetics, Breeding and Reproduction in The Plateau Mountainous Region, Ministry of Education, Guizhou University, Guiyang, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yin Zheng, College of Animal Science, Guizhou University, Mingyi Building (Teaching and Research Center), Room 428, West Campus of Guizhou University, Huaxi District, Guiyang City, Guizhou Province, 550025, People’s Republic of China, Email yzheng@gzu.edu.cnBackground: Adjusting thickening agent proportions in nanoemulsion gel (NG) balances its transdermal and topical delivery properties, making it more effective for dermatophytosis treatment.Methods: Carbomer 940 and α-pinene were used as model thickening agent and antifungal, respectively. A series of α-pinene NGs (αNG1, αNG2, αNG3) containing 0.5%, 0.75% and 1% (w/w) Carbomer 940 were developed and evaluated for stability, rheological properties, and skin irritation; assessed for ex vivo skin permeation, deposition, and fluorescent imaging of drug distribution within skin layers; and tested in vivo for efficacy against Trichophyton rubrum infection in guinea pigs, with PAS (Periodic Acid–Schiff) staining confirming fungal clearance.Results: The steady-state skin flux rates of α-pinene over 24 hours were αNG1 (46.93± 2.52 μg/cm²/h) > αNG2 (26.01± 2.65 μg/cm²/h) > αNG3 (11.36± 1.69 μg/cm²/h). The α-pinene deposition in the epidermis/dermis for αNG1 decreased substantially from 2 h (62.74 ± 3.36 μg/cm²) to 12 h (11.7 ± 2.24 μg/cm²). In contrast, αNG2 showed relatively sustained deposition with 2 h (25.54 ± 2.67 μg/cm²), 6 h (57.32 ± 4.62 μg/cm²) and 12 h (23.69 ± 3.29 μg/cm²). αNG3 exhibited a slow increase from 2 h (18.32 ± 2.11 μg/cm²) to 12 h (36.78 ± 3.22 μg/cm²). The αNG2 exhibited the highest efficacy and fungal clearance rates (71.42%, 79.17%), followed by αNG1 (55.34% and 60.42%), and αNG3(43.21%, 52.08%). Fluorescent imaging confirmed αNG2’s higher drug deposition within the epidermis/dermis, while PAS staining showed a potent fungal clearance with αNG2.Conclusion: This study demonstrates that Carbomer 940 proportions significantly impact the transdermal performance of αNG. αNG2, with a moderate proportion, optimally enhances skin drug delivery and deposition, achieving superior therapeutic outcomes. These findings highlight the importance of optimizing thickening agent proportions to improve the efficacy of topical nanoemulsion gels.Keywords: nanoemulsion gel, thickening agent proportions, drug delivery, dermatophytosis, alpha-pinene